Hydrothermal Modelling and Analysis of Sensible Heat Energy Storages for Small-scale Dwellings Considering Natural Convection. (November 2016) - Hailemariam, Henok; Wuttke, Frank
Abstract: The coupled hydrothermal behaviour of a cement-based thermal energy storage system for domestic applications is modelled under saturated conditions using the Finite Element Method along with an extensive experimental analysis program for parameter detection. For this purpose, the temperature and heat distribution of a prototype model is investigated under specific hydrothermal conditions by considering the effect of buoyancy-driven or natural convection, thus providing an accurate estimation of the loading/unloading rates and preventing the overdesign of such systems, which typically occurs when they are analysed considering conduction only by neglecting the heat transfer contribution from the buoyancy-driven convection.